ICNP® terminology subset for people with tuberculosis - Ludimila Paiva Zamprogno Silva; Cândida Caniçali Primo; Thiago Nascimento do Prado (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to develop an ICNP® terminology subset to care for people with tuberculosis. Methods: a methodological research that followed the following steps: identification and validation of empirical indicators of altered needs relevant to people with tuberculosis based on literature; cross-mapping of the empirical indicators of altered needs identified with ICNP® 2017 terms; construction of nursing diagnoses/outcomes and interventions; assessment of relevance of nursing diagnoses /outcomes and interventions and ICNP® terminology subset structuring. Results: an ICNP® terminology subset was developed to care for people with tuberculosis with 51 diagnoses/outcomes and 264 nursing interventions, assessed by nurses from Primary Health Care and structured according to Wanda Horta's Theory of Basic Human Needs. Final Considerations: the subset is a technological instrument through which it is possible to identify the elements of nursing practice from the affected human needs.